METODE PENDEKATAN SUPERVISI DALAM PENINGKATAN MUTU KURIKULUM PENDIDIKAN DI SEKOLAH MTS NEGERI BINJAI - Elvi Azizah Putri (JGK (Jurnal Guru Kita), 2022)
Supervision Approach Method In Improving The Quality Of Education Curriculum At Binjai State Mts School, Supervisors or supervisors for education in Indonesia have been established through the Regulation of the Minister of National Education of the Republic of Indonesia Number 12 of 2007 concerning supervisory standards for school supervisor The ministerial regulation emphasizes the qualifications of supervisors and the competence of supervisors at each level with the hope that the education office and regional government can recruit supervisors according to the standards that have been set. Based on the observations made by the researchers, they found problems that were not running well in the principal's academic supervision system towards teachers in MTSN Binjai, so that the impact of teacher performance was not very effective in teaching students, and the attitude of teachers did not understand and did not understand the importance of academic supervision.  to develop professional teacher competencies to advance the progress of school Education Based on the above background, the formulation of the problem in this study is "How is the Supervision Approach Method in Approaching the Quality of School Education Curriculum.